Integrated Teaching Factory Management Model For Character Development in Vocational High Schools: A Study in Rejang Lebong Regency - Sukarsih Sukarsih; Hendra Harmi; Jumira Warlizasusi (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The implementation of the Teaching Factory (TeFa) learning model in Vocational high school has developed as a key strategy to enhance the quality of industry-based vocational education. This study aims to analyze the planning, organizing, implementation, and supervision of the Teaching Factory in fostering students’ character development in vocational schools in Rejang Lebong Regency. Methodology: This research employed a descriptive qualitative approach with a case study strategy conducted in vocational high schools. Data were collected through interviews, observations, and documentation. The data were analyzed using the interactive model proposed by Miles and Huberman, which includes data collection, reduction, presentation, and conclusion drawing. Main Findings: The findings revealed that TEFA planning begins with the development of human resource planning, financial planning, production planning, and marketing planning. The organizing process involves the active participation of teachers, students, and industrial partners to create a realistic work system while instilling positive character values such as discipline, responsibility, and teamwork. A tangible form of this organizing process is the establishment of the TeFa organizational structure. Novelty/Originality of this study: The TEFA model has proven effective in cultivating work-ready character traits and supporting students’ preparedness to enter the professional and entrepreneurial sectors. These findings provide a significant contribution to the advancement of holistic, character-based vocational education in Indonesia.